LINGKUNGAN KERJA DAN KOMPENTENSI PEREKAM MEDIS TERHADAP KUALITAS SISTEM REKAM MEDIS DI RS AL ISLAM BANDUNG: Work environment and Medical Record Competency towards the Quality of Medical Record System at Al Islam Hospital - Abdul Royani (JURNAL TERAS KESEHATAN, 2019)
The effect of work environment and competence of Medical Recordes on quality ofHospital medical record file.This study aims to determine the relationship betweenwork environment and medical recorde’s competence on the quality of medicalrecord file of the hospital. The type of research in descriptive correlation withcross sectional approach. Data collection techniques used total sampling saturated sampling were 22 respondents. The result show that (1) There is still a lack ofmedical recorder knowledge about 7 medical record competetencies; (2) There isstill a lack of medical recorder involvent on hospital record quality; (3) Still lack ofacess to medical recorder in data processing quality of hospital medical record file(4) Not suitable in preseting quality data of hospital record file with expected in thefield report of report to be presented; The absence of Standard procedureoperational Disclosure of information and acess right to hospital medical recordfile quality. The result of this study the authors suggest (1) Improving theunderstanding of officers about the competencies that must be owned be the everymedical record officer about the competencies that must be owned by everymedical record files in hospitals Al-Islam Bandung; (2) Approach and lobby withelements of hospital management regarding the placement of medical record staffor provide training on the medical records to the existing officersregularly;(3)Planning and arranging effort to improve the walfare of medicalrecorders such as the ability of hospitals such as functional allowances formedical recorders;(4) conducting further research on the effect of workingenvironment and medical recorder competence on the quality of hospital medicalrecords file; (5) the result of this study can be used as reference material orpreliminary data to develop research related to medical record competence insupporting the quality of medical record file in supporting the quality of medicalrecord.